2010
DOI: 10.1007/s11936-010-0079-4
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Fatty Acids for Cardiovascular Disease Prevention

Abstract: Major dietary sources of omega-3 fatty acids are fish containing eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), as well as nuts, seeds, and vegetable oils containing α-linolenic acid (ALA). Omega-3 fatty acids, especially those derived from marine sources, may be a useful tool for the primary and secondary prevention of cardiovascular disease. Omega-3s exert their cardioprotective effects through multiple mechanisms, including reducing arrhythmias and altering production of prostaglandins, which r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 52 publications
(41 reference statements)
0
39
0
Order By: Relevance
“…According to Achremowicz and Szary-Sworst (2005), the fatty acids is special important in the diet. Therefore, polyunsaturated fatty acids (PUFA) from the n-3 and n-6 series have an influence on the nutritional quality of fish Fatty acids from the n-3 series: α-linolenic acid (C18:3, ALA), EPA (eicosapentaenoic,C20:5) and DHA (docosapentaenoic, C22:5) (Nestel, 2000, Kolanowski and Laufenberg, 2006, Sanchez-Villegas et al, 2007, DeFilippis et al, 2010 have potential beneficial human health effects. The basic fatty acid from the n-6 family is linoleic acid (C18:2, LA) which is a precursor to the other main n-6 PUFA that is arachidonic acid (C20:4 n-6, AA) (Holub andHolub, 2004, Steffens andWirth, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…According to Achremowicz and Szary-Sworst (2005), the fatty acids is special important in the diet. Therefore, polyunsaturated fatty acids (PUFA) from the n-3 and n-6 series have an influence on the nutritional quality of fish Fatty acids from the n-3 series: α-linolenic acid (C18:3, ALA), EPA (eicosapentaenoic,C20:5) and DHA (docosapentaenoic, C22:5) (Nestel, 2000, Kolanowski and Laufenberg, 2006, Sanchez-Villegas et al, 2007, DeFilippis et al, 2010 have potential beneficial human health effects. The basic fatty acid from the n-6 family is linoleic acid (C18:2, LA) which is a precursor to the other main n-6 PUFA that is arachidonic acid (C20:4 n-6, AA) (Holub andHolub, 2004, Steffens andWirth, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 20 years, randomized controlled trials and epidemiological studies have demonstrated the cardioprotective action of fish oil fatty acids, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) [4,5,6,7,8]. High intakes of EPA and DHA (>2 g/day) have shown positive effects on endothelial function, vascular reactivity, blood pressure, inflammation, and plasma lipid levels [9,10,11,12,13]. The effect of fish oil supplementation on blood glucose concentrations has been investigated and two meta-analyses concluded that the effect is marginal [14] or not statistically significant [15].…”
Section: Introductionmentioning
confidence: 99%
“…Lipids of fi sh, especially of the marine species, contain more PUFA, in particular n-3, than meat (beef, pork and veal) and vegetable oils [Givens & Gibbs, 2006;Abbas et al, 2009;DeFilippis et al, 2010]. EPA and DHA which are main representatives of n-3 fatty acids are minimally synthesised in a human organism from a plant-derived precursor, i.e.…”
Section: Introductionmentioning
confidence: 99%